Karakteristik Komposit Partikel Ijuk Mesh 40 Menggunakan Matrik Karet Dengan Variasi Komposisi Serbuk Ijuk 0 Phr,15 Phr,25 Phr Terhadap Daya Serap Radiasi Sinar Gamma - Priyono, Kukuh Suko; , Masyrukan, ST, MT (2016)
The purpose of this study is to determine how much gamma ray radiation absorption of the composite particles of 40 mesh fibers with a rubber matrix.Composite manufacturing process begins with the prepation of materials to be used,namely:palm fiber,latex soupy with dry rubber content of 60%,ZnO,ZDEC,Ionol,sulfur.Fibers are used as filler,originally from the fiber are made into powder without treatment (treatment) that could change the nature fiber own.Compound made there are 3 variations for comparison.What distinguishes the palm particle composition,without fibers,fibers 15 phr and 25 phr fibers.In the manufacture of compounds,chemicals used previously done dispersion in advance so that the chemicals are homogeneous. Dispersion is carried out 24 hours and 48 hours to sulfur.Mixing of composite materials made on a glass and stirred for 15 minutes then pour in the mold with the dimensions specified. The next process of vulcanization by using an oven and heated at a temperature of 90 o within 1 hours. The test results can be concluded composite absorption value of the composite absorption value of the highest gamma-ray radiation to the composite particles whose composition fiber by 25 phr with absorption of 39.25% the second is the composition fiber 15 phr with absorption of 37.50%,while the value of power namely the lowest absorbency without particle composite fibers,the absorption of 29.66%,Composite rubber composition larger fibers capable of absorbing radiation of gamma rays is greater than the composite rubber composition which fibers that little or no fibers